LEVEL OF DEPRESSION IN ELDERLY WITH CHRONIC DISEASES AT BLANG MANGAT PUSKESMAS, LHOKSEUMAWE CITY YEAR 2022 - Eka Sutrisna (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The aging process can cause various problems both physically-biologically, mentally and socio-economically. Changes in the elderly do not only occur physically, but also changes in mental states that are often overlooked, such as depressive disorders. About 80% of depressed elderly people who undergo treatment make a full recovery and enjoy their lives. The incidence of depression in the elderly will increase by 13.5% in the elderly who have chronic diseases and are hospitalized. The purpose of this study was to analyze the factors that influence the level of depression in the elderly with chronic diseases at the Blang Mangat Health Center, Lhokseumawe City in 2022. This type of research is descriptive. The stages of the research are: to explain how the level of depression in the elderly with chronic diseases and the factors that influence the level of depression in the elderly with chronic diseases, namely: elderly age, last education, gender, work status, family support, support for elderly cadres, types of chronic diseases experienced, and long suffering from chronic disease. The population of this study were all elderly people with chronic diseases who visited the Puskesmas. The sample in this study was the total population, that is, the entire population was sampled. Data were analyzed by descriptive analysis. The results showed that the level of depression in the elderly with chronic diseases at the Nurussalam Public Health Center was mild depression as many as 28 people (46%). It is suggested to respondents to be able to check themselves with health workers if they feel hopeless and no longer enthusiastic about living life and try to be more open to their families about the conditions experienced at this time and always think positively about the conditions of the disease they are experiencing.